2011
DOI: 10.1097/inf.0b013e31821146f7
|View full text |Cite
|
Sign up to set email alerts
|

CARESS: The Canadian Registry of Palivizumab

Abstract: The overall RSV-hospitalization rate in our study was within the range found in previous reports (1.3%-5.3%), although it did not mimic the declining rates of the US Palivizumab Outcomes Registry. This could be due to increased testing for RSV when hospitalized and increasing rates of prophylaxis of infants with underlying medical disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 37 publications
6
47
0
1
Order By: Relevance
“…During the RSV season, the limited use of palivizumab in this study population resulted in an overall frequency of 4.5% for RSV-positive hospital visits, consistent with other studies, which have reported rates of 1.1% to 8.8% among premature infants who received palivizumab. 1,8,10,11 When RSV-positive infants in the NICU were excluded, only 2.8% of the infants in this study had RSV-positive hospital visits. Therefore, a risk factor-based approach for RSV prophylaxis, limiting the use of palivizumab in infants born at 29 to 31+6/7 weeks, led to reasonable rates for RSV-positive hospital visits in this population.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…During the RSV season, the limited use of palivizumab in this study population resulted in an overall frequency of 4.5% for RSV-positive hospital visits, consistent with other studies, which have reported rates of 1.1% to 8.8% among premature infants who received palivizumab. 1,8,10,11 When RSV-positive infants in the NICU were excluded, only 2.8% of the infants in this study had RSV-positive hospital visits. Therefore, a risk factor-based approach for RSV prophylaxis, limiting the use of palivizumab in infants born at 29 to 31+6/7 weeks, led to reasonable rates for RSV-positive hospital visits in this population.…”
Section: Resultsmentioning
confidence: 91%
“…1 Among infants of Englishor French-speaking parents or legal guardians with a gestational age of 29 to 32 weeks in the Canadian Registry of Palivizumab (CARESS), only 1.25% were hospitalized with RSV. 8 Because Fraser Health cares for an ethnically diverse population, a significant proportion of families would have been excluded from the CARESS registry. 8 There has been wide variation in the frequency of RSVpositive hospitalizations reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Some evidence of palivizumab's benefit has been reported in groups of infants in Cana da, but it was not from a randomized placebo-controlled trial. 6 Challenges in administering the drug relate to the strict four-week injection intervals and the need to recalculate the dose at each visit, which are magnified in northern Canada. These challenges and concerns of cost have led to palivizumab being recommended in high-risk populations only.…”
mentioning
confidence: 99%